Diagnosis of toxoplasma infection in cardiac transplant recipients using the polymerase chain reaction. Issue 10 (October 1992) - Holliman, R; Johnson, J; Savva, D; Cary, N; Wreghitt, T
Abstract : Cardiac biopsy samples taken from transplant recipients around the time of primary toxoplasma infection were investigated by conventional histology and amplification of the P30 gene of Toxoplasma gondii by the polymerase chain reaction (PCR). Toxoplasma was detected more frequently by PCR than histology which may reflect the enhanced sensitivity of the former technique. Further studies are required to determine the optimal amount of tissue which should be examined by each technique and to develop a PCR assay capable of distinguishing between quiescent infection and active toxoplasmosis.